Use of cone-beam computed tomography to characterize urinary bladder variations and optimize delivery of radiation therapy for canine bladder cancer - Nieset, Jessica Rae, author; Harmon, Joseph F., advisor; Bailey, Susan M., committee member; LaRue, Susan M., committee member; Worley, Deanna R., committee member; Johnson, Thomas E. (Thomas Edward), 1964-, committee member (Colorado State University. Libraries, 2011)
Urinary bladder cancer is the most common cancer of the canine urinary tract, with transitional cell carcinoma (TCC) being the most commonly diagnosed tumor type. TCC is aggressive, invasive and fatal for most dogs. If left untreated, TCC of the canine bladder has average survival times less than one year. Optimal treatment of this malignancy remains a topic of debate. Different treatment options exist, but many complicating factors make the probability of cure very low, regardless of treatment type, and most care is palliative in nature. Radiation therapy is a possible treatment option, however dailyshape, size, and positional changes (motion) of the bladder and surrounding soft tissue structures often make this modality difficult to incorporate into a curative-intent treatment plan. This study was designed to investigate and quantify the motion characteristics experienced by the canine urinary bladder from day to day. Additionally, this information was then used to examine possible treatment scenarios and determine which of those scenarios would be optimal for canine bladder cancer patients. Retrospective cone beam CT (CBCT) image data from ten dogs were used in this study. Organs of interest were contoured on each daily treatment CBCT data set and the images, along with the contours, were registered (fused) to the original (reference) planning CT. Quantification of bladder motion was determined by making measurements relative to the planning CT. Dosimetric data for the organs of interest were determined using dose volume histograms generated from sample treatment plans. Results indicate a wide range in bladder motion throughout treatment, which partly depends on the methods used for patient positioning (set-up). Of the three patient positioning methods evaluated (dorsal, sternal, and lateral recumbency), the least amount of bladder variability, as well as lowest rectal dose, is seen when dogs are placed in lateral recumbency. Using these motion characteristics, we were able to develop different treatment planning and set-up scenarios that allow for a curative dose to be delivered to the bladder, while simultaneously reducing the dose delivered to the nearby sensitive rectal tissue. All advanced treatment planning techniques produce a better dose distribution than traditional parallel opposed planning, with adaptive radiation therapy (ART) planning techniques showing the most advantageous dose distribution. These results allow for a more informed approach to the treatment of canine bladder cancer, as well as providing possible curative-intent treatment options for canine patients with this malignancy.
Keywords: canine bladder cancer; radiation therapy